Atypical immunoglobulin light chain amyloidosis: Spontaneous vertebral compression fracture, liver involvement, and bone marrow involvement report of 3 cases and review of the literature. Issue 36 (September 2016) - Wu, Xia; Feng, Jun; Cao, Xinxin; Zhang, Lu; Zhou, Daobin; Li, Jian
Abstract: Background: Primary immunoglobulin light chain amyloidosis (AL amyloidosis) is a plasma cell disorder which mainly affects heart, kidneys, liver, and peripheral nervous system. Cases of atypical AL amyloidosis presented as spontaneous vertebral compression fractures have been rarely reported, and data about the management and clinical outcomes of the patients are scarce. Methods: Herein, we present 3 new cases of AL amyloidosis with spontaneous vertebral compression fracture and review 13 cases retrieved from the literature. Results: Moreover, we observed overrepresentations of liver involvement and bone marrow involvement in AL amyloidosis with spontaneous vertebral compression fracture. Conclusion: We believe that better awareness of the rare clinical presentation as spontaneous vertebral compression fracture of AL amyloidosis can facilitate earlier diagnosis and earlier treatment.